PELATIHAN DESAIN GRAFIS SEBAGAI UPAYA PENINGKATAN SOFT SKILL DAN KEMANDIRIAN DALAM ERA DIGITAL 4.0 - Kezia Noviani Anou; Zakaria Victor Kareth; Ego Srivajawaty Sinaga; Hubertus Ngaderman (JURNAL PENGABDIAN PAPUA, 2023)
Nies World's learning house is a place where several youths gather to hone their skills. Some of the classes that were opened were music, language, photography and so on. As for some youths who are experiencing financial constraints, they are given capital for entrepreneurship such as selling squeezed oranges and raising pigs. Graphic design class is one of the activities that have been carried out at the Nies World Learning House with the aim of improving soft skills for young people. This activity began with a discussion with the youth regarding the interest and interest in design. The activity was continued by designing T-shirts and digital invitations through their respective cellphones. The content in the design consists of writing combined with lines, images and text. The results of each youth's design are printed on the selected T-shirts. It can be seen that the soft skill potential of the youth is very good if it continues to be developed and sharpened again so that it can improve the quality of designs that have economic value.Keywords: design; digital; enterpreunership; skill; t-shirtÃ‚Â